ENERGY SUSTAINABILITY: presentation and discussion of the indicators - Gesinaldo Ataíde Cândido (HOLOS, 2016)
Energy is considered one of the main resources for the development of sites, as well as for economic sectors and activities, however, their generation and use forms of may have negative consequences for development, particularly for social and environmental issues. In this context, there is a need to explore energy issues from the perspective of sustainability and implementation of indicators. Similarly, the objective of this article is to identify in the academic and institutional sources of energy sustainability indicators that can be used to measure the energy sustainability of most generating energy sources. In methodological terms, it is a literature search, which eight of these are used ANEEL (1999), AFGHAN (1999); ISED (2001); BERMANN (2002), HELIO INTERNATIONAL (2005), Oliveira et al. (2006), Souza (2010) and BORGES (2012). The results show a total of 135 indicators which, after analysis within specific criteria, completed a total of 61 indicators divided into the following dimensions: social, environmental, economic, technological, political, territorial and cultural.